A methodological comparative analysis of monetary policy and trade openness on economic growth in West Africa: Does language play a role? - Seth Acquah Boateng; Bridgette Enimil; Ebenezer Takyi-Danquah (PLoS ONE, 2026)
The study examines the effect of monetary policy and trade openness on economic growth in the ECOWAS countries. Using panel regression analysis and the Random Forest algorithm from the machine learning technique, the study reveals the existence of a major difference between the two language communities. The expansion of the broad money supply has a highly positive effect on economic growth in the two language communities; the impact is much greater in the Francophone countries. But trade openness has contradictory associations; it is positive in the Francophone countries and negative in the Anglophone countries. The Random Forest approach outperforms the standard econometric approach in terms of predictive accuracy (R² = 67.56%), thereby confirming the existence of non-linear associations. The evidence of major differences is linked to the existence of different post-colonial institutions; that is, the common CFA currency institutions in the Francophone countries and the independent national monetary policies in the Anglophone countries. The study implies that ECOWAS countries require distinct policies instead of standard policies.